Lost in Text: A Cross-Genre Analysis of Linguistic Phenomena within Text - Chiara Buongiovanni; Francesco Gracci; Dominique Brunato; Felice Dell’Orletta (IJCoL)
Moving from the assumption that formal, rather than content features, can be used to detect differences and similarities among textual genres and registers, this paper presents a new approach to linguistic profiling – a well-established methodological framework to study language variation – which is applied to detect significant variations within the internal structure of a text. We test this approach on the Italian language using a wide spectrum of linguistic features automatically extracted from parsed corpora representative of four main genres and two levels of complexity for each, and we show that it is possible to model the degree of stylistic variance within texts according to genre and language complexity.